2000
DOI: 10.1046/j.1365-2230.2000.00608.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of viral warts with cimetidine: an open-label study

Abstract: The immunomodulatory actions of cimetidine, an H2-receptor antagonist, and its use in the treatment of viral warts has been described previously but its effectiveness is still debated. We report the results in 47 patients with multiple, nongenital viral warts who were treated with oral cimetidine in a 3-month open-label study. The drug was generally well tolerated and 87% of children and 68% of adults improved with treatment. Follow-up data in 65% of the patients showed that there had been no recurrence in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 11 publications
(18 reference statements)
0
22
0
5
Order By: Relevance
“…Periungual warts, in particular, are known for the high recurrence rate and recalcitrance and thus present a treatment challenge. A wide range of treatment modalities have been used for warts including cryotherapy1, laser therapy2-4, immunotherapy5,6 and intralesional bleomycin7, among many others. While many of the treatments have limitations in practice due to pain and scarring, especially for those of periungual locations, recent reports have demonstrated that topical immunotherapy with diphenylcyclopropenone (DPCP) is a safe and effective treatment modality of recalcitrant warts, which includes the periungual types for its painless application and absence of scarring8-10.…”
Section: Introductionmentioning
confidence: 99%
“…Periungual warts, in particular, are known for the high recurrence rate and recalcitrance and thus present a treatment challenge. A wide range of treatment modalities have been used for warts including cryotherapy1, laser therapy2-4, immunotherapy5,6 and intralesional bleomycin7, among many others. While many of the treatments have limitations in practice due to pain and scarring, especially for those of periungual locations, recent reports have demonstrated that topical immunotherapy with diphenylcyclopropenone (DPCP) is a safe and effective treatment modality of recalcitrant warts, which includes the periungual types for its painless application and absence of scarring8-10.…”
Section: Introductionmentioning
confidence: 99%
“…59 Cimetidine has been well tolerated and has achieved clearance of treatmentresistant, nongenital warts in children. 60 10-25. 64 The vaccines are administered in a series of 3 injections, with the second dose 1-2 months after the first dose, and the third dose 6 months after the first dose.…”
Section: Immunomodulatorsmentioning
confidence: 99%
“…As stated in the initial review article, cimetidine efficacy has been shown in open-label studies for the treatment of warts, but randomized placebo-controlled studies showed no difference between cimetidine and placebo. [5][6][7][8][9] Therefore, the failure of his 2 cases to respond to cimetidine is not surprising. As suggested in our review, the lack of controlled studies in patients with GV presents a challenge in assessing the true role of most therapeutic interventions for this condition.…”
Section: Replymentioning
confidence: 99%